SISTEM PENUNJANG KEPUTUSAN OPTIMALISASI BARANG DENGAN ALGORITMA GREEDY PADA PT SENTRALINDO TEGUH GEMILANG - Susi Rianti; Hendarman Lubis; Reza Pahlevi (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2020)
AbstractThe purpose of this research is to optimize the preparation of goods into trucks so that time and energy are not wasted on PT. Sentralindo Teguh Gemilang engaged in shipping goods. In preparing goods at PT. STG uses experts. But in the preparation of the goods, I guess I will use a type of truck where all items will be included. This makes the company need more time and money. To solve this, the author uses the Greedy algorithm to make the preparation of items more efficient. And apply it to the decision support system. The results of this application show a decrease in time and energy in the preparation of goods or in other words there is an optimization of energy and time in the preparation of goods. Keywords: item preparation optimization, Greedy algorithm, penyusunan barang, preparation of goods ,   PT  Sentralindo Teguh Gemilang